Declining the interpreter’s role in World War I - Cowley, Peter James (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
In this article I will examine autobiographical and fictionalised accounts of World War One by three French interpreters: the writer André Maurois, the painter Paul Maze, and the cartoonist Hansi. All three worked as officiers de liaison with the British Expeditionary Force, discharging their duties in remarkably divergent ways and accounting for them equally differently. My focus will be on how their accounts can be read as representations of the role of the interpreter, and at the same time how the figure of the interpreter, underpinned by the assumption of neutrality, is deployed to represent other activities in conflict zones.